2019
DOI: 10.3389/fphys.2019.00579
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of the New Method Sarcoplasma Stimulating Training Versus Traditional Resistance Training on Total Training Volume, Lactate and Muscle Thickness

Abstract: Background: Trained subjects have difficulty in achieving continued results following years of training, and the manipulation of training variables through advanced resistance training (RT) methods is widely recommended to break through plateaus. Objective: The purpose of the present study was to compare the acute effects of traditional RT (TRT) versus two types of sarcoplasma stimulating training (SST) methods on total training volume (TTV), lactate, and muscle thickness (MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
(32 reference statements)
0
13
0
Order By: Relevance
“…The next step is to reduce the external load by 20% and perform an additional set with a 4/0/1/0 tempo; following a 20 s rest interval, 20% of the external load is reduced again, and a set with 4/0/1/0 tempo is completed to volitional fatigue. In the last set, the load is further decreased by 20% and after its completion, following a 20 s rest interval, a static hold is performed (e.g., at 90 • of elbow flexion) to volitional fatigue [53]. Another SST variation refers to the performance of eight sets of exercises at 70−80% 1RM to volitional fatigue with programmed rest intervals between subsequent sets (45,30,15,5,5,15,30, and 45 s) without reducing the load [53].…”
Section: Drop Sets and Sarcoplasma Stimulating Training Techniquementioning
confidence: 99%
See 3 more Smart Citations
“…The next step is to reduce the external load by 20% and perform an additional set with a 4/0/1/0 tempo; following a 20 s rest interval, 20% of the external load is reduced again, and a set with 4/0/1/0 tempo is completed to volitional fatigue. In the last set, the load is further decreased by 20% and after its completion, following a 20 s rest interval, a static hold is performed (e.g., at 90 • of elbow flexion) to volitional fatigue [53]. Another SST variation refers to the performance of eight sets of exercises at 70−80% 1RM to volitional fatigue with programmed rest intervals between subsequent sets (45,30,15,5,5,15,30, and 45 s) without reducing the load [53].…”
Section: Drop Sets and Sarcoplasma Stimulating Training Techniquementioning
confidence: 99%
“…Another SST variation refers to the performance of eight sets of exercises at 70−80% 1RM to volitional fatigue with programmed rest intervals between subsequent sets (45,30,15,5,5,15,30, and 45 s) without reducing the load [53]. Similarly, to drop sets, the main aim of SST is to induce high metabolic stress [53]. Recently, de Almeida et al [53] demonstrated that SST resulted in greater acute biceps brachii and triceps brachii muscle thickness when compared to a traditional set scheme in trained subjects, even when total training volume was higher in a traditional set scheme RT.…”
Section: Drop Sets and Sarcoplasma Stimulating Training Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…Another common measure, surface EMG, is a non-invasive tool used to evaluate muscle activation ( Gabriel et al, 2006 ). Finally, B-mode ultrasound is a validated method for measuring MT, which is correlated with muscle cross-sectional area, a hypertrophy parameter ( Ema et al, 2013 ; Timmins et al, 2016 ), as well as acutely assessing skeletal muscle cell swelling in response to a RT bout ( de Almeida et al, 2019 ). Intriguingly, a recent study by Hirono et al (2020) found that acute measures of muscle cell swelling were positively correlated with chronic increases in muscle hypertrophy.…”
Section: Introductionmentioning
confidence: 99%